Design of Alip Seafood Accounting System Based on Microsoft Access - Haris Yukie; Serly Serly (Universitas Internasional Batam, 2024)
Alip Seafood is an enterprise that engaged in the sale of fresh fish established in 1995. Since the establishment of the company, the company still uses traditional bookkeeping that records its financial transactions manually. The traditional bookkeeping is inefficient and ineffective in generating financial reports for the owner to make financial decisions. Thus, this study aizms to an accounting system that can record transactions and generate financial statements automatically and accurately. The system designed for Alip Seafood is based on Microsoft Access. The data used in this research were collected through interviews, observation, and documentation. This system is capable of recording transactions and generating financial statements accurately. The system also allows the owner of Alip Seafood to view other information such as stocks in inventory, purchase report, sales report, lists of customers, lists of suppliers, and accounts payable report. This project is expected to help the owner understand its financial position and performance so that the owner can make the right financial decisions that can support its sustainability. The recommendation for future research is to provide more innovative and useful solutions to other enterprises.